2022
DOI: 10.3390/dermatopathology9030025
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-Pemphigoid Gestationis Eruption Following SARS-CoV-2 Vaccination with mRNA Vaccine

Abstract: Auto-immune reactions, including auto-immune bullous disease, have been reported following SARS-CoV-2 virus vaccination. Few cases of bullous pemphigoid are described, but there has been no case of pemphigoid gestationis. We report the first case here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Recently, another case of what was termed pseudo-PG has been described 3 days following administration of the second dose of the Pfizer-BioNTech COVID-19 vaccine. 7 Since the introduction of COVID-19 mRNA vaccines, cases of postvaccination BP, BP-like eruptions, and pemphigus vulgaris have been described. [8][9][10][11] Tomayko et al 10 reported 12 cases of subepidermal eruptions, including BP, in which 7 patients developed blisters after the second dose of either the Pfizer-BioNTech or Moderna mRNA vaccine.…”
mentioning
confidence: 99%
“…Recently, another case of what was termed pseudo-PG has been described 3 days following administration of the second dose of the Pfizer-BioNTech COVID-19 vaccine. 7 Since the introduction of COVID-19 mRNA vaccines, cases of postvaccination BP, BP-like eruptions, and pemphigus vulgaris have been described. [8][9][10][11] Tomayko et al 10 reported 12 cases of subepidermal eruptions, including BP, in which 7 patients developed blisters after the second dose of either the Pfizer-BioNTech or Moderna mRNA vaccine.…”
mentioning
confidence: 99%